MODEL ALOMETRIK BIOMASSA DAN MASSA KARBON BAMBU BELANGKE (Gigantochloa pruriens Widjaja.) DI HUTAN RAKYAT DESA SIRPANG SIGODANG, KECAMATAN PANEI, KABUPATEN SIMALUNGUN - Yonri Situmorang; Muhdi Muhdi; Irawati Azhar (Peronema Forestry Science Journal, 2016)
Bamboo has a high carbondioxide absorption, but quantitively this ability of bamboo belangke (Gigantochloa pruriens Widjaja.) has not much known. This research was conducted in the area of forest community Sirpang Sigodang village, Panei Sub District, Simalungun District. The research was carried out in two stages, namely the first stage were to data in the field and the second stage was analyze of biomass and carbon plant in the laboratory. Parameters measured in the field was wet weight, where as in the laboratory is measured moisture content, volatile matter content, ash content and carbon content. The results showed that the best model of alometric equations for estimating biomass and carbon of bamboo belangke (Gigantochloa pruriens Widjaja.) was W = 38.258-10.683D+0.854D2 and C = 14.994-4.139D+0.339D2. The potential of biomass and carbon contained in bamboo belangke (Gigantochloa pruriens Widjaja.) were 8.67 ton/ha and 4.05 ton C/ha. Keywords: Allometric Models, Babu belangke (Gigantochloa pruriens Widjaja), community forest, Sirpang Sigodang Viilage.